Reflections in a bloodshot lens : America, Islam and the war of ideas - Pintak, Larry (Pluto, 2006)
There exists today a tragic rift between Americans and the world's Muslims. Each views the other with suspicion and anger. Yet in the immediate aftermath of 9/11, there was widespread sympathy for the U.S. in the great arc of Muslim nations from West Africa to Southeast Asia. This book explores what happened. It examines the disconnect that leads Americans and Muslims around the world to view the same words and images in fundamentally different ways. Partly a result of a centuries-old 'us' against 'them' dichotomy and an essential difference in worldview, the problem is exacerbated by an increasingly polarised media and by leaders on both sides who either don't understand or don't care what impact their words and policies have in the world at large. Journalist-scholar Lawrence Pintak, a former CBS News Middle East correspondent, argues that the Arab media revolution and the rise of "patriot-journalists" in the US marginalized voices of moderation, distorting perceptions on both sides of the divide with potentially disastrous results. Built on the author's extensive journalistic experience, the book is carefully grounded in contemporary academic scholarship -- including Orientalism, othering, worldview, media effects theory and framing theory, amongst others -- giving it broad appeal to policymakers, students of such fields as media studies, Middle East studies and Islamic studies, and general current affairs readers